PENGEMBANGAN LKPD BERBASIS PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA MATERI CAHAYA DAN OPTIK KELAS VIII - Aneke Fransiska Karunia; Noer Af’idah (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2022)
Teaching materials that are widely used are worksheets because they can be arranged according to the needs of students. Based on the results of the distribution of student questionnaires for class VIII MTs. Syafi’iyah Pulorejo prefers discussion/group learning. worksheets used in MTs. Syafi’iyah Pulorejo is a publication from a publisher that is unable to facilitate discussion/group learning activities. Light and opticals materials are considered difficult by students because of the calculation material, especially science teachers MTs. Syafi’iyah Pulorejo still uses conventional methods. This study aims to produce worksheets based on cooperative learning type think pair share on light and optics for class VIII. This research includes development research that uses the ADDIE model through the analyze, design, development, and evaluation stages. The results of the development are worksheets with an average validity value of 98,33% by material experts, 85% by media experts, and 98,33 % by science teacher MTs. Syafi’iyah Pulorejo. From the three validators, an average validity value of 93, 89% was obtained with very valid criteria.